Mauritania : guidelines for a four-year development program - Westebbe, R.M; International Bank for Reconstruction and Development (Mauritania : International Bank for Reconstruction and Development, 1968)
The report evaluates the first Four - Year Plan and recommends another four year program of action, as guidelines for the next four year plan, which will be prepared by the Mauritanian Government
Is a reversed version of 1967
Report of a mission organized by the International Bank for Reconstruction and Development at the request of the Islamic Republic of Mauritania
MF23/01/2019
Loans
Keywords: Mauritania